أثر جائحة كورونا على سلاسل الامداد العالمية - عماد, بروبة; بالعيد, خير الدين; عدنان, بسر (جامعة الوادي - University of Eloued, 2023)
تهدف هذه الدراسة إلى التعرف على أثر جائحة كورونا في أداء سلاسل الامداد العالمي وذلك من خلال الاطلاع على الاحصائيات المتعلقة بالنقل الدولي بعد جائحة كورونا، وتحليل البيانات المتاحة، حيث استخدمت هذه الدراسة المنهج الوصفي عن طريق استقراء الدراسات، الأبحاث، الكتب والمقالات العربية والأجنبية التي تمت في جائحة كورونا وسلاسل الامداد العالمي، والمنهج التحليلي من خلال تحليل البيانات التي تتوافر عن إشكالية الدراسة وفي إطار الإشارة إلى الواقع العالمي. وقد توصلت هذه الدراسة أن جائحة كورونا كشفت عن مواطن الضعف في سلاسل الإمداد بسبب عدم كفاءة التخطيط ونقص المرونة لدى العديد من طبقات سلاسل الإمداد بالإضافة إلى عدم كفاية التنويع في استراتيجيات التوريد. "This study aims to investigate the impact of the Corona pandemic on global supply chains by examining statistics related to international transportation after the pandemic. It analyzes the available data using a descriptive methodology, which involves reviewing Arab and foreign studies, research, books, and articles conducted during the Corona pandemic and global supply chains. The study also employs an analytical method to analyze data related to the research problem and to highlight the global reality. The findings of this study indicate that the Corona pandemic has revealed weaknesses in supply chains due to inefficient planning and lack of flexibility in various layers of the supply chains. Additionally, there is insufficient diversification in sourcing strategies. "
Keywords: جائحة كورونا، سلاسل امداد دولي، نقل بحري، نقل جوي.; Corona pandemic, international supply chains, maritime transport, air transport.